Accelerated organics degradation by peroxymonosulfate activated with biochar co-doped with nitrogen and sulfur. (August 2021) - Oh, Wen-Da; Zaeni, Julia Raudlatul Jannah; Lisak, Grzegorz; Lin, Kun-Yi Andrew; Leong, Kah-Hon; Choong, Zheng-Yi
Abstract: Engineered biochar is increasingly regarded as a cost-effective and eco-friendly peroxymonosulfate (PMS) activator. Herein, biochar doped with nitrogen and sulfur moieties was prepared by pyrolysis of wood shavings and doping precursor. The doping precursor consists of either urea, thiourea or 1:1 w/w mixture of urea and thiourea (denoted as NSB-U, NSB-T and NSB-UT, respectively). The physicochemical properties of the NSBs were extensively characterized, revealing that they are of noncrystalline carbon with porous structure. The NSBs were employed as PMS activator to degrade organic pollutants particularly methylene blue (MB). It was found that NSB-UT exhibited higher MB removal rate with k app  = 0.202 min −1 due to its relatively high surface area and favorable intrinsic surface moieties (combination of graphitic N and thiophenic S). The effects of catalyst loading, PMS dosage and initial pH were evaluated. Positive enhancement of the MB removal rate can be obtained by carefully increasing the catalyst loading or PMS dosage. Meanwhile, the MB removal rate is greatly influenced by pH due to electrostatic interactions and pH dependent reactions. The NSB-UT can be reused for several cycles to some extent and its catalytic activity can be restored by thermal treatment. Based on the radical scavenger study and XPS analysis, the nonradical pathway facilitated by the graphitic N and thiophenic S active sites are revealed to be the dominant reaction pathway. Overall, the results of this study show that engineered biochar derived from locally available biowaste can be transformed into PMS activator for environmental applications. Graphical abstract: Image 1 Highlights: Biochar co-doped with nitrogen and sulfur was prepared using wood shavings. Physicochemical properties of the doped biochar were comprehensively studied. Graphitic N and thiophenic S were endowed into the biochar for efficient PMS activation. Doped biochar prepared with 1:1 w/w% urea and thiourea has the best catalytic activity. Mechanism of PMS activation involving MB is dominated by the nonradical pathway.